Plasma pharmacokinetics and muscle disposition of marbofloxacin in chickens - Urzúa Pizarro, Natala Francisca (2016)
Background: Reports on the pharmacokinetics of marbofloxacin in birds are scarce, even when it is a useful tool in poultry production. OBJECTIVES: Determining marbofloxacin kinetic parameters in plasma and muscle arrangement after intravenous and oral administrations and establishing its withdrawal period. METHODS: Clinical healthy chickens (1.08±0.22‌ kg) were used as experimental subjects, formed in groups of 5. In Group A (n= 45) birds received 2 mg/kg of marbofloxacin intravenously while group B (n= 65) was given the same oral dose after fasting for 12 hours. Blood samples in the groups and 5 g of muscle were obtained at different times, in A group up to 24 hours and in B group until 120 hours after application. Once the samples were obtained and treated, marbofloxacin was quantified by HPLC. RESULTS: Marbofloxacin in fasted chickens is almost completely absorbed (F= 97%), mean residence time is moderate (6.9 hours), with a high volume of distribution. Orally, mean residence time is less in plasma (4.9 hours) and the withdrawal time was calculated 2.5 days. CONCLUSIONS: The kinetic results are consistent with those presented by other fluoroquinolones in poultry and are in line with short production cycles in chickens.